2020
DOI: 10.2459/jcm.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan use in a real-world population of patients with heart failure and reduced ejection fraction

Abstract: Aims Practice guidelines recommend sacubitril/valsartan for heart failure with reduced ejection fraction. The aim of our study was to describe the use of sacubitril/valsartan in real-world clinical practice to help identify patients best able to tolerate titration to higher doses. Methods We retrospectively analyzed clinical data for 201 patients with heart failure with reduced ejection fraction prescribed sacubitril/valsartan at our heart failure clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Twenty‐one articles, 10 retrospective and 11 prospective, were selected 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 (Supporting Information, Figure S1 and Tables S2 and S3 ). Collectively, these studies included 16 952 patients: 12 082 (71.3%) were accounted for by a single article, 16 while the sample size of the other ones varied from 11 (0.06%) to 2037 (12.0%) subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐one articles, 10 retrospective and 11 prospective, were selected 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 (Supporting Information, Figure S1 and Tables S2 and S3 ). Collectively, these studies included 16 952 patients: 12 082 (71.3%) were accounted for by a single article, 16 while the sample size of the other ones varied from 11 (0.06%) to 2037 (12.0%) subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these studies included 16 952 patients: 12 082 (71.3%) were accounted for by a single article, 16 while the sample size of the other ones varied from 11 (0.06%) to 2037 (12.0%) subjects. 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Four investigations included patients in NYHA class I (Lopez‐Azor 23 : 1.1%; Vicent 18 : 1.2%; Kakuzna 11 : 3.0%; and Pharithi 24 : 10.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Comparison of Sacubitril/Valsartan Versus Enalapril on Effect on NT-proBNP in Patients Stabilized From an Acute Heart Failure Episode (PIONEER-HF) study of acute HFrEF, a single case of hyponatraemia was reported in the enalapril group, which was not observed with sacubitril/valsartan 28. Two cases of sacubitril/valsartan-induced hyponatraemia were described29 30; however, observational studies show either no significant long-term changes or even some increase in serum sodium with sacubitril/valsartan, suggesting that it might prevent rather than trigger hyponatraemia 31–33…”
Section: Inhibition Of Renin-angiotensin and Neprilysin Pathwaysmentioning
confidence: 99%
“…The MECKI score has been shown to be able to differentiate between HFrEF patients able, or not able, to tolerate high dose sacubitril/valsartan dosing long term. 9 This may well be true of other risk scores for HFrEF, as it is plausible they can all predict sickest, highest risk patients, because of advanced age, low blood pressure or poor renal function, or the presence and severity of other co-morbidities. Nonetheless it is an important finding for it shows the potential of the MECKI score to be used in routine practice in aiding clinical decision making, predicting which patients will likely tolerate certain drug therapies.…”
Section: Other Uses Of the Mecki Scorementioning
confidence: 99%